Comparison of the accuracy of intraoral scanning systems with conventional impression in full dentate patient - Alsayed, İmadettin (My University, 2018)
Tüm Dişleri Mevcut Hastalarda Konvansiyonel Ölçü Ve İntraoral Dijital Taramanın Netliğinin Karşılaştırılması.Amaç: Son senelerde, direkt dijitalizasyon için farklı intraoral tarama sistemleri ortaya çıktı. Ancak bu tarayıcılarının netliği değişkendir, ve hakkındaki bilgiler yetersizdir. Bu çalışmanın amacı iki farklı intraoral tarama sisteminin, alt ve üst çene arasındaki netliğinin farkının karşılaştırılmasıdır.Materyal ve Method: 10 adet eksik dişi bulunmayan hastanın her birinden bir adet PVS (Elite HD+, Zhermack SpA, Italy) materyali ile ölçü alındı, ve 3 adet alt-üst çene taraması CEREC OC(Sirona Dental Systems, Sirona, Bensheim, Germany) ve Straumann CARES IOS(Intra oral Scanner, Basel, Switzerland) ile yapıldı. Konvansiyonel ölçü döküldü ve elde edilen alçı model taratılarak referans model olarak netlik ve doğruluk kıyaslamasında kullanıldı. Netlik değerlendirilmesindeki deviasyonlar diğer ölçülerin birbiri üzerine çakıştırılması metodu ile gözlemlendi. Dijital ölçü dosyaları STL formatına dönüşütürülerek (Geomagic Control; 3D Systems. USA) ile işlendi ve analiz edildi.Bulgular: Doğruluk değerleri , CEREC OC için üst çene 99,88±42, alt çene için, 82,6±26,81 μm. CARES IOS için üst çene için 105,53±25,49 μm, alt çene için 109,56±36,84 μm dur. Iki sistem arasındaki fark istatiksel olarak anlamlı değildir (P>0.05). Netliğin farkı istatiksel olarak anlamalıdır (P<0.05), CEREC OC alt ve üst çenede daha yüksek değerler gösterdi.Sonuç: CEREC OC netlik olarak CARES IOS sisteminden daha üstün bulunurken doğruluk seviyesi her iki sistemde de benzerdir. Alt ve üst çeneler arasında her iki sistemde istatistiksel olarak anlamlı fark bulunmamıştır.

2.ENGLISH SUMMARYComparison of The Accuracy of Intraoral Scanning Systems with Conventional Impression in Full Dentate Patient. Imadettin ALSAYED, Dr. Öğr Üyesi. Umut ASLAN, Department of ProsthodonticsAim: Over the last years, different intraoral scanning systems for direct digitalization have been introduced to the dental market. However, the accuracy of these scanners is variable, and little information is available. The aim of this in vivo study was to compare the accuracy of two intraoral scanning systems and the difference between upper and lower jaw on the accuracy.Material and Method: 10 patients with full dentition received one conventional impression with polyvinyl siloxane (PVS) (Elite HD+, Zhermack SpA, Italy) and three scans with CEREC OC (Sirona Dental Systems, Sirona, Bensheim, Germany) and Straumann CARES IOS (Intra oral Scanner, Basel, Switzerland) for upper and lower jaw. The conventional impresions were poured and the casts made from it were scanned and used as the reference model to evaluate precision and trueness of intraoral scanning virtual models provided by each system. Impression files were converted to STL files and processed and analyzed using (Geomagic Control; Geomagic, Morrisville, USA).Results: The trueness value was 99,88±42,56 μm in upper jaw and 82,6±26,81 μm in lower jaw for CEREC OC, and 105,53±25,49 μm in upper jaw, and 109,56±36,84 μm in lower jaw for CARES IOS. The differences between two systems were not statistically significant (P>0.05), but statistically significant difference was found in the precision (P<0.05). CEREC OC showed higher value in both upper and lower jaws.Conclusions: CEREC OC was more precise than CARES IOS and at the similar level of trueness. No statistically significant difference was found between upper and lower jaws in both systems.
Keywords: Accuracy; CAD/ CAM; CAD/ CAM Intraoral scanning; Dental Prosthesis; Diş Protezleri; Intraoral tarama; Netlik; STL dosya; STL files